Dynamics of Population Happiness Level Between Archipelagic and Non-Archipelago Provinces In Indonesia - Ahmad, Abdul Chalid; Amin, Chairullah; Suprihartiningsih, Erna; Abae, Irawan (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Welfare has a fundamental dimension related to the level of happiness. Therefore, from the perspective of development success, welfare indicators should be able to describe the condition of better happiness of the population between regions in a country. Recently, the measure of the population's happiness level has become an indicator of welfare with a broader dimension. One of them is through the happiness index. This study aims to analyze the differences in the dynamics of the population's happiness level between island and non-island provinces in Indonesia, during 2014-2021. This dynamic is thought to be influenced by the poverty level, quality of human development, unemployment rate, and income distribution between community groups. The analysis method used is panel data from 34 provinces, including eight island provinces and 26 non-island provinces. After passing the model specification and classical assumption tests, the estimation model applies a fixed effect model with the Panel Estimation General Least Squares (EGLS) method. The results of the model estimation found that the unemployment rate did not have a significant effect on the happiness index. Meanwhile, the poverty rate, human development index, and Gini Ratio had a positive and significant effect. It was also found that there were differences in the dynamics of happiness levels between island and non-island provinces, as a result of changes in the independent variables in the model.